2010
DOI: 10.1007/s12192-010-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

N-terminally fusion of Her2/neu to HSP70 decreases efficiency of Her2/neu DNA vaccine

Abstract: DNA vaccines consisted of tumor-associated antigen (TAA) are well suited for immunotherapy against tumor. The construct can contain TAA fused to an appropriate molecule (biologic adjuvant) to improve the efficacy of anti-tumor immune response. Heat shock protein 70 (HSP70) has been shown to be an excellent candidate, capable of cross-priming TAA by antigen presenting cells leading to a robust T-cell response. However, the relationship between strong T-cell responses and tumor rejection is not always mutually e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…N-terminally fusion of Her2/neu to gp96 C-terminal domain might have caused conformational change or steric hindrance, which resulted in the decrease of Her/neu DNA vaccine efficiency, consistent with previous report (Pakravan et al 2010b). It was previously shown that the signal sequence at the beginning of Her2 sequence have critical role in the potency of Her2 DNA vaccine (Wei et al 1999).…”
Section: Since Cd8supporting
confidence: 89%
“…N-terminally fusion of Her2/neu to gp96 C-terminal domain might have caused conformational change or steric hindrance, which resulted in the decrease of Her/neu DNA vaccine efficiency, consistent with previous report (Pakravan et al 2010b). It was previously shown that the signal sequence at the beginning of Her2 sequence have critical role in the potency of Her2 DNA vaccine (Wei et al 1999).…”
Section: Since Cd8supporting
confidence: 89%
“…We previously reported that N-terminally fusion of Her2/ neu to HSP70 (pHSP70/He2) decreased the efficiency of Her2/neu DNA vaccine (Pakravan et al 2010b). Tumor progression and IFN-γ/IL-4 levels were similar to that of pNT/Her2, but pHSP70/Her2 decreased Treg percentage at the tumor site and, importantly, increased survival rate.…”
Section: Discussionmentioning
confidence: 97%
“…We previously (Pakravan et al 2010a) demonstrated that fusion of GP96 C-terminal to Her2 could raise IL-4/IFN-γ level, which was concomitant with better control of tumor growth. Another study revealed that administration of HSP70 and Her2 (Pakravan et al 2010b) led to tumor progression while IL-4/IFN-γ level was much more than that of GP96 C-terminal fused to Her2. Presumably, there is an optimum range and balanced level for IL-4/IFN-γ.…”
Section: Discussionmentioning
confidence: 99%